Detection of Growth-Restricted Fetuses During Pregnancy Is Associated With Fewer Intrauterine Deaths But Increased Adverse Childhood Outcomes: An Observational Study. Issue 6 (June 2021) - Andreasen, L. A.; Tabor, A.; Nørgaard, L. N.; Rode, L.; Gerds, T. A.; Tolsgaard, M. G.
Abstract : (Abstracted from BJOG 2021;128:77–85) Fetal growth restriction (FGR) is associated with a number of adverse outcomes, including stillbirth, need for early delivery, and long-term neurodevelopmental problems. Identifying FGR early allows for heightened monitoring of the fetus in utero and during labor and for planning an appropriate time for delivery.